2013
DOI: 10.1097/opx.0b013e3182968c77
|View full text |Cite
|
Sign up to set email alerts
|

Demodex

Abstract: Following a clinical sequence helps identify Demodex, the underdiagnosed, undertreated, and underappreciated ocular surface disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
22
0
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 30 publications
0
22
0
1
Order By: Relevance
“…However, the detection of Demodex spp. on eyelashes accompanied by cylindrical dandruff increases the possibility of detection [7]. A study by Randon et al [48] using in vivo confocal microscopes (IVCM) showed the reliability and effectiveness for the detection of ocular demodicosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the detection of Demodex spp. on eyelashes accompanied by cylindrical dandruff increases the possibility of detection [7]. A study by Randon et al [48] using in vivo confocal microscopes (IVCM) showed the reliability and effectiveness for the detection of ocular demodicosis.…”
Section: Discussionmentioning
confidence: 99%
“…The symptoms accompanying demodicosis are slight redness and dryness of the skin, as well as conjunctivitis, dysfunction of Meibomian glands, and dry eye syndrome [4,5,6,7]. Demodex folliculorum occur in clusters near the roots of eyelashes and hair follicles, whereas D. brevis usually occurs singly in sebaceous glands and Meibomian glands [8].…”
Section: Introductionmentioning
confidence: 99%
“…Characteristic collarettes or cylindrical dandruff (CD) around the eyelash base are considered to be a sign ocular demodicosis [2]. Demodex has a recognised association with anterior blepharitis and is believed to play a role in the perpetuation of ocular surface inflammation and dry eye disease [3][4][5]. Recently, numerous treatment [6,7] and diagnostic [3,8,9] options have emerged.…”
Section: Introductionmentioning
confidence: 99%
“…Demodex has a recognised association with anterior blepharitis and is believed to play a role in the perpetuation of ocular surface inflammation and dry eye disease [3][4][5]. Recently, numerous treatment [6,7] and diagnostic [3,8,9] options have emerged. While the topical application of tea tree oil (Melaleuca alternifolia) is the most commonly agreed management strategy [7], a consensus on the optimal diagnostic technique for confirming mite presence, is lacking.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation